RESERVOIR DISTRIBUTION AND DEPOSITIONAL MODEL ANALYSIS OF TALANG AKAR FORMASTION: CASE STUDY KL FIELD OFFSHORE NORTH WEST JAVA - RAMDAN, DADAN
Talang Akar formation in Offshore North West Java (ONWJ) is considered to have significant remaining hydrocarbon potential which currently unexplored because of several limitations as follows: poor seismic data quality due to multiple carbonate layers/build-ups in the overburden (Parigi, Pre-Parigi, Baturaja), shallow gas, fault shadow etc. In geology, TAF target is dominated by deltaic system which might appears as non continuous event on the seismic data. Thin reservoir in the relatively deep buried has made the reservoir within tuning thickness zone. It leads to the more complex problem. Therefore, TAF become very difficult to be mapped. The successful exploration activities of TAF in 80’-90’s, Most of them were based on the structural high which discovered multiple reservoirs with good quality in that present structural high. Every proposed well become very uncertain without supported by seismic image and geological understanding. Consequently, there is still some remaining work to optimize the research of TAF potential. Understanding of the existing data is very critical to define any alternative method to be utilized. The use of seismic phase with some control wells and flattened technique on the proper horizon has exhibited geological phenomena of the TAF in the area. Combined with amplitude extraction, the result is expected to explain more detail of reservoir existences in present structural high. The interpretation of the data indicates that multiple reservoirs on the present structural high as a result of possible infill incision process associated with syndepositional fault activity of rifting process. Amplitude extraction from phase based interpreted horizons indicates good correlation between amplitude and gross reservoir thickness from wells. Paleo-geography of the area is interpreted as incised valleys fill fluvial deltaic system associated with fault activity and erosion located in the edge of the basin. Geological reconstruction was built to model the geological process and mechanism in the area. This model shows valley incision and its deposits associated with uplift and subsidence mechanism during rifting process. The continuous of domino block process causes continuous of subsidence and uplift of the connected sub-basin. This mechanism is believed to expose deposited reservoir in low relief area become on the current structural high.